Scientific Assessment of the Welfare of Dry Sows Kept in Individual Accommodations - Curtis, Stanley E.; Baker, Rodney B.; Estienne, Mark J.; Lynch, P. Brendan; McGlone, John J.; Pedersen, Bjarne K. (Council for Agricultural Science and Technology (CAST), 2009)
The use of individual gestation accommodations (IGAs) for dry sows in commercial pork production is an issue that has raised much debate. Public perceptions and misconceptions of welfare issues have the potential to dramatically impact swine production. The nine-member international task force of this new issue paper critically evaluates the scientific evidence of IGAs for sows, including considerations for behavior, nutrition and feeding, reproduction, clinical examination and health, manure management, worker safety, and system design. The authors indicate that no compelling evidence exists from scientific evaluations and comparisons of dry-sow keeping systems that, overall, either individual or group accommodation is more appropriate than the other.
Keywords: Dry Sows; Pork Production; Inidividual Gestation Accomodations